Prognostic value of CA125 in advanced heart failure patients - Monteiro, S (2009)
INTRODUCTION: Serum levels of CA125 are often high in advanced heart failure (AHF) patients. AIM: To determine the predictive value of CA125 in forecasting the occurrence of death or cardiac transplantation in an AHF population. METHODS: 88 AHF patients referred for heart transplantation were divided into 2 groups based on CA125 levels: normal (CA125<38 U/mL) and elevated (>/=38 U/mL). Events (death or heart transplant) were monitored over a period of 13+/-7 months after CA125 determination. RESULTS: Patients with elevated CA125 (n=65) had significantly lower blood pressure, body mass index, serum sodium and peak exercise oxygen consumption, while B-type natriuretic peptide levels were significantly higher. The combined primary endpoint (death or heart transplant) rate was 39.4% and 62.3% in normal and elevated CA125 groups, respectively (p=0.029). Multivariate regression analysis showed that CA125 and sodium levels were the only independent predictors of the combined endpoint. CONCLUSION: In AHF patients, plasma CA125 was an effective prognostic marker. Its determination may contribute to better risk stratification in this population.